PABPN1 as a pan-cancer biomarker: prognostic significance and association with tumor immune microenvironment - Li, Hong-Xing; Ma, Xiao-Ling; Ma, Wang-bin; Jia, Tian-Yu; Sun, Xiao-Hong; He, Xiao-Xia; Zhang, Li-li; Xi, Ya-Ming (Frontiers in Immunology, 2025)
ObjectiveThis study aimed to investigate the role of poly(A) binding protein nuclear 1 (PABPN1) as a potential pan-cancer biomarker for prognosis and immunotherapy.MethodsThe original datasets were acquired from TCGA and GEO databases. PABPN1 expression analysis was conducted utilizing the Oncomine, TIMER, GEPIA, and BioGPS databases. Prognostic implications of PABPN1 were assessed through GEPIA, Kaplan-Meier plotter, and the PrognoScan database. Correlations between PABPN1 expression and immune checkpoints (ICP), tumor mutational burden (TMB), microsatellite instability (MSI), and neoantigens in human cancers were examined using the SangerBox database. Additionally, the association between PABPN1 and marker genes of tumor-infiltrated immune cells in urogenital cancers was confirmed. Differential expression of PABPN1 in urogenital cancers with distinct clinical characteristics was assessed using the UALCAN database. Finally, experiments of T24, 5637, HLF and MCF-7 cells were performed to verify the above results.ResultsThe expression of PABPN1 tended to be higher in human cancers compared to paired normal tissues. Its expression levels showed strong associations with TMB, MSI, and neoantigens. Additionally, significant correlations existed between PABPN1 expression and tumor immune-infiltrated cells (TILs) in many human cancers, with marker genes of TILs showing significant relationships with PABPN1 expression, particularly in urogenital cancers. The coexpression networks of PABPN1 were predominantly involved in the regulation of immune response, antigen processing, and presentation. After down expression of PABPN1, mRNA expression levels of MRPS15 and GPx (Glutathione peroxidase) decreased significantly in T24, 5637 HLF and MCF-7 cells.ConclusionPABPN1 was expected to be an important role element in cancer research, serving as a potential prognostic and immunological pan-cancer biomarker.